Investigation on the effect of venturi geometry variation on microbubble generation - Niellambare, N.; H. H., Mohamad; Erny Afiza, Alias; Nasrul Hadi, Johari (AIP Publishing, 2022)
Venturi nozzle is the simplest method in generating microbubble (MB). However, direct relation between venturi geometry variation and generated bubbles properties namely, bubble mean diameter (BMD) and dissolved oxygen (DO) level remains ambiguous. Thus, this study investigates the effect of outlet angle variation, gas intake and water flowrate on the BMD and DO level. Visualization experiments were performed on six geometry variant of venturi nozzles with fixed inlet angle (19°) and outlet angle of 8°,10° and 12° for Venturi with air intake and 5°, 12° and 45° for Venturi without air intake condition. In addition, the venturi nozzles also tested in varied flowrate of 13, 33 and 66 litre per minute (LPM). As the results, with the increment of outlet angle, the BMD decreases while the DO level increases in all nozzles. The presence of air intake in the nozzles produces larger MBs. Furthermore, The BMD and DO level is proportional to the water flowrate. Overall, the varied geometry parameters induce a difference in BMD which affects the DO level.